Ethical perceptions of accounting students in a Portuguese university: the influence of individual factors and personal traits - Costa, Alberto J. (2016)
Our purpose is to empirically examine whether gender, age, work experience, and attendance of a course on ethics affect the ethical perceptions of Portuguese accounting students and analyze the influence of some individual factors that may affect their ethical decision-making. Additionally, we consider the degree of importance assigned to a list of personal traits and their relationship with those factors. We concluded that gender influenced the degree of importance attributed by students to initiative/entrepreneurship, obedience, and responsibility; age influenced the degree of importance attributed by students to integrity; work experience influenced the degree of importance attributed by students to obedience; and attendance of a course on ethics influenced the degree of importance attributed to independence. For each of these factors, the influence did not prove to be statistically significant in decision-making. Similarly, the study identified some reservations regarding attitudes the students’ peers might have, and when asked about this, they had negative opinions, believing their colleagues would have lower ethical standards. Our results add to the literature, especially because, in Portugal, little has been done to understand which factors may affect students’ ethical decision-making processes. We expect to bring added value to stakeholders, teachers, and scholars engaged with these matters.